Learning Malware Analysis: Explore the Concepts, Tools, and Techniques to Analyze and Investigate Windows Malware - K A, Monnappa (Packt Publishing, Limited, 2018)
Malware analysis and memory forensics are powerful analysis and investigation techniques used in reverse engineering, digital forensics, and incident response. This book teaches you the concepts, tools, and techniques to determine the behavior and characteristics of malware using malware analysis and memory forensics.